2015
DOI: 10.1128/aac.00052-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Efficacy of Amphotericin B Combined with Posaconazole against Experimental Disseminated Sporotrichosis

Abstract: bWe evaluated the combination of posaconazole with amphotericin B in vitro and in a murine model of systemic infections caused by Sporothrix brasiliensis and Sporothrix schenckii sensu stricto. In vitro data demonstrated a synergistic effect, and although posaconazole alone was effective against sporotrichosis, efficacy in terms of survival and burden reduction was increased with the combination. This combination might be an option against disseminated sporotrichosis, especially when itraconazole or amphoteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…The in vitro and in vivo activity of posaconazole against Sporothrix spp. is well known [21,24]; however, its high costs compromises usage in lower-income countries of South America, like Brazil, where sporotrichosis also figures as a higly prevalent mycosis.…”
Section: Plos Onementioning
confidence: 99%
“…The in vitro and in vivo activity of posaconazole against Sporothrix spp. is well known [21,24]; however, its high costs compromises usage in lower-income countries of South America, like Brazil, where sporotrichosis also figures as a higly prevalent mycosis.…”
Section: Plos Onementioning
confidence: 99%
“…after the onset of antifungal treatment. Previous studies have shown that some therapeutic protocols may reduce the fungal burden in sporotrichosis, even when the infection is caused by S. brasiliensis [ 10 , 11 , 12 , 13 ]. Recently, Souza et al [ 13 ] reported a significant reduction in the fungal burden within 5 to 11 weeks after start of antifungal treatment in cats with sporotrichosis caused by S. brasiliensis .…”
Section: Introductionmentioning
confidence: 99%
“…Ketoconazole is not used as much given its low efficacy and potentially severe side effects (13,16). Among the newer triazoles, in vivo and in vitro activity has been reported with posaconazole in combination with amphotericin B, while voriconazole has not been considered a therapeutic choice for these infections due to its high MICs (19,20).…”
mentioning
confidence: 99%